Photocatalyst, preparation method and application thereof, and method for producing ammonia by reducing NO through photocatalysis

By combining Pd and Cu elements on the HxMoO3-y photocatalyst, the oxygen vacancies electrons are transferred using the Schottky junction effect, the catalytic activity and selectivity of the photocatalyst are improved, and the problem of insufficient NO catalytic activity at room temperature in the prior art is solved, and an efficient NO reduction and ammonia production process is achieved.

CN119549160AActive Publication Date: 2025-03-04CHINA PETROLEUM & CHEMICAL CORP +1
View PDF 7 Cites 0 Cited by

Patent Information

Application Number
CN202311125587.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2023-09-01
Publication Date
2025-03-04
Estimated Expiration
2043-09-01

AI Technical Summary

Technical Problem

The existing photocatalytic activity and selectivity of NO at room temperature, and the precious metal components are high, and the local electrons in semiconductor materials are lacking, resulting in low catalytic efficiency.

Method used

Using HxMoO3-y photocatalyst combined with Pd and Cu elements, electrons on surface oxygen vacancies are transferred to PdCu alloy through the Schottky junction effect under light, adjusting the surface and electron structure, and improving catalytic activity and selectivity.

Benefits of technology

It is achieved efficient catalytic reduction of NO at room temperature to produce ammonia, with NH3 selectivity close to 98.0%, yield reaching 28.2 molgcat-1h-1, and the catalyst has excellent stability and alkali resistance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119549160A_ABST
    Figure CN119549160A_ABST
Patent Text Reader

Abstract

The invention relates to the field of photocatalysis, and discloses a photocatalyst, a preparation method and application thereof, and a method for producing ammonia by reducing NO through photocatalysis. The photocatalyst comprises HxMoO3-y, a Pd element and a Cu element, x is greater than 0 and less than or equal to 1, y is greater than or equal to 0 and less than 3, and based on the total amount of the photocatalyst, the content of the Pd element is 5-12 mol%, and the content of the Cu element is 0.9-9 mol%. The photocatalyst has improved catalytic activity and selectivity.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of photocatalysis, and in particular to a photocatalyst, a preparation method and application thereof, and a method for photocatalytic reduction of NO to generate ammonia. Background Art

[0002] Nitrogen oxides (NO x ) is a major greenhouse gas and air pollutant, causing environmental and health problems. x The reduction technologies include selective catalytic reduction (SCR) and selective non-catalytic reduction (SNCR), but these processes are carried out at high temperatures (>150℃ for SCR and >800℃ for SNCR), which requires considerable energy. x It is the main component of NO, formed by combustion processes in chemical plants, power plants, etc. Although existing thermal catalytic methods have made great efforts to reduce the temperature, it is still difficult to achieve a high NO removal rate at room temperature. In addition, ammonia (NH 3 ) is not only the main component of fertilizer, but also the storage 2 The most common NH 3 The synthesis method is the classic Haber-Bosch process, which requires extreme conditions of high temperature and high pressure. Therefore, photocatalytic reduction of NO to ammonia at room temperature is crucial to solving the energy and environmental crises facing mankind. However, due to the weak adsorption capacity of NO on active sites and the large number of side reactions, the development of highly active and selective photocatalysts is particularly urgent.

[0003] CN107790127A relates to a Pt-Ag / WO 3 Plasma photocatalyst and its preparation method and application. The photocatalyst is a Pt-Ag noble metal alloy nanoparticle modified with WO having a plasma resonance effect. 3 The plasma photocatalyst has high utilization efficiency of ultraviolet light and visible light in sunlight; at the same time, by changing the composition of the precious metal alloy Pt-Ag, the energy band structure of the photocatalyst can be adjusted, thereby improving the photocatalytic performance of the photocatalyst. The photocatalyst prepared in this application has good photocatalytic removal efficiency for low-concentration NO gas, and the photocatalytic removal reaction is carried out at room temperature, which is simple to operate and has low energy consumption. Its shortcomings are: Pt and Ag are both precious metals, the preparation cost is high, WO 3 The semiconductor lacks local electrons, the catalytic efficiency is low, and the high value-added product NH 3 The yield and selectivity are not high.

[0004] Plasmonic photocatalysts reported in the literature have weak adsorption of gas molecules, lack of local electrons, and low catalytic efficiency. In recent years, the introduction of oxygen vacancies (OVs) with abundant local electrons in semiconductors has been considered as a key method for capturing and activating CO 2 , O 2 or N 2 Professor Zhang's team first reported that the oxygen vacancies in BiOBr nanosheets have abundant localized electrons, which can significantly promote the N 2 adsorption and activation, increasing N 2 Reduction to NH under visible light irradiation 3 The efficiency of (MAO C, WANGJ, ZOU Y, et al. Hydrogen Spillover to Oxygen Vacancy of TiO 2-x H y / Fe:Breaking theScaling Relationship of Ammonia Synthesis[J].Journal of the American Chemical Society,2020,142(41):17403-17412.). Compared with other plasma semiconductors, hydrogen molybdenum bronze (H-MoBronze) with rich OVs x MoO 3-y ) exhibits strong plasmon absorption in the visible light spectrum, which is caused by strong localized surface plasmon resonance (LSPR). However, in the photocatalytic reaction, H x MoO 3-y The OVs on the surface can be easily oxidized by holes in the valence band, resulting in activation termination of gas molecules and low catalytic efficiency. Summary of the invention

[0005] The purpose of the present invention is to overcome the above problems existing in the prior art and to provide a photocatalyst and a preparation method and application thereof as well as a method for photocatalytic reduction of NO to generate ammonia, wherein the photocatalyst has improved catalytic activity and selectivity.

[0006] In order to achieve the above object, the present invention provides a photocatalyst in a first aspect, wherein the photocatalyst comprises H x MoO 3-y , Pd element and Cu element, 0<x≤1, 0≤y<3, wherein, based on the total amount of the photocatalyst, the content of the Pd element is 5-12 mol %, and the content of the Cu element is 0.9-9 mol %.

[0007] Preferably, the total molar content of the Pd element and the Cu element is 10-13%, preferably 11-12%.

[0008] Preferably, the molar ratio of the Pd element to the Cu element is 1-10:1.

[0009] A second aspect of the present invention provides a method for preparing a photocatalyst, the method comprising the following steps:

[0010] (1) providing a mixed solution containing a molybdenum precursor, a Pd precursor, a Cu precursor, a structure directing agent, a reducing agent, and an ion exchanger;

[0011] (2) The precursor material obtained from the mixed solution in step (1) is washed and then calcined in a hydrogen atmosphere.

[0012] Preferably, the preparation of the mixed solution in step (1) comprises:

[0013] (1-1) mixing a molybdenum precursor dispersion with a Pd precursor and a Cu precursor;

[0014] (1-2) The mixed solution obtained in step (1-1) is mixed with a structure directing agent, a reducing agent and an ion exchanger.

[0015] The third aspect of the present invention provides a photocatalyst prepared by the method described in the second aspect.

[0016] A fourth aspect of the present invention provides use of the above-mentioned photocatalyst in photocatalytic reduction of NO to generate ammonia.

[0017] A fifth aspect of the present invention provides a method for photocatalytic reduction of NO to generate ammonia, the method comprising: contacting a photocatalyst with a NO-containing gas under light irradiation conditions, wherein the photocatalyst is the photocatalyst described in the first aspect or the third aspect above.

[0018] The photocatalyst provided by the present invention adopts H x MoO 3-y , Pd and Cu elements, H x MoO 3-y The electrons enriched on the surface OVs can be quickly transferred to the PdCu alloy through the Schottky junction under light, which not only improves the stability of the OVs, but also acts as an active site to regulate the surface and electronic structure of the PdCu alloy, exhibiting a synergistic multi-level coupling effect by integrating different components, thereby improving the photocatalytic activity and ammonia selectivity.

[0019] The photocatalyst of the present invention, under full spectrum irradiation, NH 3 The selectivity is close to 98.0% and the yield can reach 28.2 molg cat -1 h -1 The catalyst has a considerable efficiency in separating photogenerated carriers and can process NO gas with different concentrations and NH3 The photocatalyst preparation method provided by the present invention has a simple process, is green and environmentally friendly, and can be used in large-scale production. BRIEF DESCRIPTION OF THE DRAWINGS

[0020] Figure 1 The PdCu / H prepared in Example 1 x MoO 3-y Transmission electron microscopy (TEM) image of the photocatalyst;

[0021] Figure 2 The PdCu / H prepared in Example 1 x MoO 3-y TEM images of the photocatalyst and the corresponding energy dispersive X-ray spectroscopy (EDS) images;

[0022] Figure 3 X-ray diffraction (XRD) patterns of the photocatalysts prepared in Examples 1-3 and Comparative Examples 1-3;

[0023] Figure 4 The X-ray photoelectron spectroscopy (XPS) graphs of the photocatalysts prepared in Examples 1-3 and Comparative Examples 1-3 are shown; wherein (a) is the Mo 3d XPS spectrum of the photocatalyst prepared in Comparative Example 1, (b) is the Mo 3d XPS spectrum of the photocatalyst prepared in Comparative Example 2, (c) is the Mo 3d XPS spectrum of the photocatalyst prepared in Comparative Example 3, and (d) is the Mo 3d XPS spectrum of the photocatalyst prepared in Comparative Example 3. 3 (e) is the Mo 3d XPS spectrum of the photocatalyst prepared in Example 1; (f) is the Mo 3d XPS spectrum of the photocatalyst prepared in Example 2; (g) is the Mo 3d XPS spectrum of the photocatalyst prepared in Example 3;

[0024] Figure 5 The X-ray photoelectron spectroscopy (XPS) graphs of the photocatalysts prepared in Examples 1-3 and Comparative Examples 1-3; wherein (a) is the O 1s XPS spectrum of the photocatalyst prepared in Comparative Example 1, (b) is the O 1s XPS spectrum of the photocatalyst prepared in Comparative Example 2, (c) is the O 1s XPS spectrum of the photocatalyst prepared in Comparative Example 3, and (d) is the O 1s XPS spectrum of the MoO 3 (e) is the O 1s XPS spectrum of the photocatalyst prepared in Example 1; (f) is the O 1s XPS spectrum of the photocatalyst prepared in Example 2; (g) is the O 1s XPS spectrum of the photocatalyst prepared in Example 3;

[0025] Figure 6X-ray photoelectron spectroscopy (XPS) graphs of the photocatalysts prepared in Examples 1-3 and Comparative Examples 1-2; wherein (a) is a Pd 3d XPS spectrum of the photocatalysts prepared in Example 1 and Comparative Example 1, (b) is a Pd 3d XPS spectrum of the photocatalysts prepared in Examples 2-3, (c) is a Cu 2p XPS spectrum of the photocatalysts prepared in Example 1 and Comparative Example 2, and (d) is a Cu 2p XPS spectrum of the photocatalysts prepared in Examples 2-3;

[0026] Figure 7 The photocatalysts prepared in Example 1 and Comparative Examples 1-3 were heated at 350°C and H 2 UV / Vis-NIR diffuse reflectance spectra after reduction;

[0027] Figure 8 Electron spin resonance (ESR) spectra of the photocatalysts prepared in Example 1 and Comparative Examples 1-3;

[0028] Fig. 9 The photocatalysts prepared in Examples 1-5 and Comparative Examples 1-3 were NH 3 and NH 2 OH production rate;

[0029] Fig.10 The apparent quantum yield of the photocatalyst prepared in Example 1 under the irradiation of monochromatic light, the UV-vis diffuse reflectance spectrum, varies with wavelength;

[0030] Fig.11 The photocatalysts prepared in Example 1 and Comparative Examples 1-3 were NH 3 and NH 2 OH production rate;

[0031] Fig.12 The photocatalytic activity of the photocatalyst prepared in Example 1 under different NO concentration conditions;

[0032] Fig.13 The photocatalyst prepared in Example 1 produces NH 3 Cyclic test;

[0033] Fig.14 The photocatalytic activity of the photocatalysts prepared in Example 1 and Comparative Examples 1-3 in alkali metal solutions;

[0034] Fig.15 The photocatalytic activities of the photocatalysts prepared in Example 1 and Comparative Examples 1-3 in heavy metal solutions. DETAILED DESCRIPTION

[0035] The endpoints and any values ​​of the ranges disclosed in this article are not limited to the precise ranges or values, and these ranges or values ​​should be understood to include values ​​close to these ranges or values. For numerical ranges, the endpoint values ​​of each range, the endpoint values ​​of each range and the individual point values, and the individual point values ​​can be combined with each other to obtain one or more new numerical ranges, which should be considered as specifically disclosed in this article.

[0036] In the present invention, the H x MoO 3-y It has the conventional meaning in this field, and the present invention has no special limitation on it. It can also be called hydrogen molybdenum bronze.

[0037] A first aspect of the present invention provides a photocatalyst, wherein the photocatalyst comprises H x MoO 3-y , Pd element and Cu element, 0<x≤1, 0≤y<3, wherein, based on the total amount of the photocatalyst, the content of the Pd element is 5-12 mol %, and the content of the Cu element is 0.9-9 mol %.

[0038] According to a preferred embodiment of the present invention, based on the total amount of the photocatalyst, the content of the Pd element is 5.5-12 mol %, and the content of the Cu element is 1-6 mol %.

[0039] Preferably, the total molar content of Pd and Cu is 10-13%, more preferably 11-12%. The total molar content of Pd and Cu in this preferred embodiment can not only improve the catalytic performance of the photocatalyst, but also help control costs.

[0040] In the photocatalyst of the present invention, the contents of Pd and Cu are measured by inductively coupled plasma optical emission spectroscopy (ICP-OES).

[0041] In the present invention, H x MoO 3-y The existence of can be determined by XRD (X-ray diffraction) characterization. The values ​​of x and y can also be determined by comparing the XRD spectrum of the photocatalyst with the standard spectrum.

[0042] Preferably, the molar ratio of Pd element to Cu element is 0.5-12:1, preferably 1-10:1, for example 1:1, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, 10:1. This preferred embodiment can achieve the effect of synergistically promoting the synthesis of ammonia by the plasma resonance effect and the PdCu alloy effect.

[0043] According to the present invention, preferably, the Pd element and the Cu element are at least partially present in the form of a PdCu alloy. This preferred embodiment is more conducive to the PdCu and H x MoO 3-y The synergistic effect is exerted to improve the effect of synthesizing ammonia. It should be noted that the photocatalyst provided by the present invention does not exclude the existence of some Pd elements and Cu elements in other forms (such as simple substances).

[0044] According to a preferred embodiment of the present invention, Pd and Cu are dispersed in H x MoO 3-y On the nanosheet, preferably, the Pd element and the Cu element are at least partially present in the form of alloy nanoparticles.

[0045] According to a preferred embodiment of the present invention, the x MoO 3-y The size of PdCu particles on the nanosheets is 2-10 nm.

[0046] The PdCu particles are not particularly limited in their form, and may be, for example, spherical.

[0047] The morphology of the photocatalyst can be determined by TEM characterization. Figure 1 It can be seen that in H x MoO 3-y PdCu nanoparticles with a size (~5 nm) and shape similar to spheres were deposited on the nanosheets.

[0048] In the present invention, the presence of Pd and Cu in the form of a PdCu alloy can be determined by TEM and corresponding energy dispersive X-ray spectroscopy (EDS), for example, by Figure 2 It can be seen that PdCu / H x MoO 3-y The spatial distribution of Pd and Cu elements in the hybrid is the same. Figure 1 and Figure 2 The formation of PdCu alloy is fully demonstrated.

[0049] According to the present invention, preferably, the XRD spectrum of the photocatalyst does not contain diffraction peaks of Pd and Cu. In the photocatalyst having such preferred characteristics, Pd and Cu are highly dispersed in H x MoO 3-y Therefore, the catalyst has further improved ammonia synthesis performance.

[0050] According to the present invention, preferably, as characterized by XPS, in the photocatalyst, (O -OH +O H2O ) / O total The molar ratio of O is 0.6-0.65, preferably 0.6-0.63; wherein O-OH is the -OH group coordinated with the Mo atom, O H2O -OH coordinated with Mo atom 2 Group, O total The photocatalyst provided by the present invention has a higher (O -OH +O H2O ) / O total The ratio of H + The higher the degree of intercalation, the better the catalytic performance in synthetic ammonia.

[0051] In the present invention, (O -OH +O H2O ) / O total The molar ratio of can be obtained by X-ray photoelectron spectroscopy (XPS) characterization through the peak area ratio. Specifically, according to the O 1s XPS spectrum of the photocatalyst, there are three peaks, namely, -OH coordinated with Mo atoms at 532.4 eV 2 (O H2O ) group, -OH group coordinated to Mo atom at 531.4 eV (O -OH ) and the lattice O atom coordination group (O latt ), O total O H2O , O -OH , O latt The sum of .

[0052] According to a preferred embodiment of the present invention, the photocatalyst is heated to 350°C and H 2 After reduction, UV / Vis-NIR diffuse reflection showed that there was an LSPR absorption peak at 540nm±2nm. This indicates that PdCu alloy can promote the formation of MoO during H overflow. 3 The generation of oxygen vacancies in the nanostructured carbon nanotubes induces a stronger plasma absorption peak.

[0053] A second aspect of the present invention provides a method for preparing a photocatalyst, the method comprising the following steps:

[0054] (1) providing a mixed solution containing a molybdenum precursor, a Pd precursor, a Cu precursor, a structure directing agent, a reducing agent, and an ion exchanger;

[0055] (2) The precursor material obtained from the mixed solution in step (1) is washed and then calcined in a hydrogen atmosphere.

[0056] According to the method provided by the present invention, preferably, the photocatalyst prepared by the method comprises H x MoO 3-y, Pd element and Cu element, and preferably the Pd element and the Cu element are at least partially present in the form of a PdCu alloy.

[0057] The present invention has no particular limitation on the manner of providing the mixed solution in step (1), and the principle is to facilitate the dispersion of the various substances. As long as a mixed solution in which the various substances are evenly dispersed can be obtained, the performance of the catalyst can be further improved.

[0058] Preferably, the preparation of the mixed solution in step (1) comprises:

[0059] (1-1) mixing a molybdenum precursor dispersion with a Pd precursor and a Cu precursor;

[0060] (1-2) The mixed solution obtained in step (1-1) is mixed with a structure directing agent, a reducing agent and an ion exchanger.

[0061] Preferably, step (1-1) comprises mixing a molybdenum precursor and water, and then heating the mixture in a water bath under stirring to obtain the molybdenum precursor dispersion.

[0062] According to a preferred embodiment of the present invention, the concentration of the molybdenum precursor in its aqueous solution is 10-30 g / L.

[0063] According to a preferred embodiment of the present invention, the conditions for water bath heating include: water bath temperature of 70-90° C., and heating time of 20-40 min.

[0064] The above preferred embodiment is more conducive to obtaining a molybdenum precursor dispersion with better dispersibility.

[0065] The mixing of the molybdenum precursor dispersion with the Pd precursor and the Cu precursor in step (1-1) is preferably carried out under stirring conditions.

[0066] According to a preferred embodiment of the present invention, the method further comprises, before step (1-2), allowing the mixed solution obtained in step (1-1) to stand (preferably for 0.5-5 hours), and then performing step (1-2). There is no particular limitation on the standing time, provided that the Pd and Cu active components can be fully dispersed and loaded on the molybdenum precursor substrate.

[0067] The mixing in step (1-2) is preferably carried out under stirring (eg magnetic stirring).

[0068] The present invention has no particular limitation on the stirring conditions, which are based on the conditions that are more conducive to dispersion. Those skilled in the art can make appropriate selections according to the specific types of materials.

[0069] According to the method provided by the present invention, the types of the structure directing agent, the reducing agent and the ion exchanger are selected so as to be able to prepare a molecule containing H x MoO 3-y , Pd element and Cu element catalyst.

[0070] Preferably, the structure directing agent is a directing agent that is conducive to obtaining a PdCu alloy. Further preferably, the structure directing agent is an alloy structure directing agent, preferably polyvinyl pyrrolidone (PVP).

[0071] In the present invention, the reducing agent is used to reduce Pd and Cu ions. Preferably, the reducing agent is L-ascorbic acid.

[0072] In the present invention, the ion exchanger is used to obtain Pd 0 CuO. Preferably, the ion exchanger is potassium bromide.

[0073] The present invention has a wide selection range for the molybdenum precursor, as long as it can provide H x MoO 3-y The Mo in the molybdenum precursor can be selected from at least one of molybdenum trioxide, ammonium molybdate and sodium molybdate.

[0074] Preferably, the Pd precursor is selected from at least one of sodium chloropalladate, palladium chloride and palladium nitrate;

[0075] Preferably, the Cu precursor is selected from at least one of copper chloride, copper nitrate, copper acetate and copper sulfate.

[0076] According to a preferred embodiment of the present invention, the molar ratio of the Pd precursor to the Cu precursor is 0.5-12:1, preferably 1-10:1, for example, 1:1, 2:1, 3:1, 4:1, 5:1, 6:1, 7:1, 8:1, 9:1, 10:1, calculated as metal elements. The present invention adjusts the feed ratio of the two metal sources of copper and palladium to adjust the performance of the obtained catalyst material, thereby achieving the effect of synergistically promoting the synthesis of ammonia by the plasma resonance effect and the PdCu alloy effect.

[0077] Preferably, the amount of the Pd precursor, the Cu precursor and the molybdenum precursor is such that the total molar content of the Pd element and the Cu element in the prepared photocatalyst is 10-13%, preferably 11-12%, based on the total amount of the photocatalyst. Based on the present disclosure, those skilled in the art know how to adjust the amount of the Pd precursor, the Cu precursor and the molybdenum precursor.

[0078] In the present invention, the amount of the structure directing agent, reducing agent and ion exchanger can be selected in a wide range, based on the ability to achieve their respective purposes.

[0079] In the present invention, preferably, relative to the total added amount of 0.4 mmol of Pd precursor and Cu precursor, the amount of the structure directing agent used is 100-300 mg, for example, 100 mg, 150 mg, 200 mg, 250 mg, 300 mg.

[0080] In the present invention, preferably, relative to the total amount of 0.4 mmol of the Pd precursor and the Cu precursor added, the amount of the reducing agent used is 100-300 mg, for example, 100 mg, 150 mg, 200 mg, 250 mg, 300 mg.

[0081] In the present invention, preferably, relative to the total amount of 0.4 mmol of the Pd precursor and the Cu precursor added, the amount of the ion exchanger used is 500-700 mg, for example, 500 mg, 550 mg, 600 mg, 650 mg, 700 mg.

[0082] The use of the above preferred amount of additives is more conducive to promoting the formation of PdCu alloy.

[0083] According to a preferred embodiment of the present invention, the method further comprises, before step (2), removing the structure directing agent, the reducing agent and the ion exchanger in the mixed solution of step (1), and then standing (preferably standing for 1-5 hours) to obtain the precursor material. In the present invention, specifically, the structure directing agent, the reducing agent and the ion exchanger can be removed by centrifugation (e.g., ultrapure water centrifugation).

[0084] The present invention has no particular limitation on the specific operation of washing in step (2), the purpose of which is to remove the unreacted materials and / or impurities existing on the surface of the obtained precursor material.

[0085] According to a preferred embodiment of the present invention, in step (2), the washing agent used in the washing is an organic solvent. The washing agent can be a conventional choice in the art, and the preferred washing agent is ethanol.

[0086] Preferably, the method further comprises drying after the washing and then the calcining. The drying conditions preferably include: a drying temperature of 50-80°C, a vacuum degree of -3000 to -1000 kPa, and a drying time of 4-10 hours.

[0087] According to the present invention, preferably, the calcination conditions in step (2) include: a temperature of 200-400° C. and a calcination time of 0.5-2 h.

[0088] According to the present invention, preferably, the hydrogen-containing atmosphere is provided by hydrogen and an optional inert gas. The present invention has no particular limitation on the content of hydrogen in the hydrogen-containing atmosphere, but is preferably not less than 50% by volume, preferably 80-100% by volume. The inert gas can be selected by conventional means, including but not limited to nitrogen, argon, helium and neon.

[0089] The preparation method of the present invention is simple and feasible, with low energy consumption. The obtained catalyst material has strong stability and adaptability in use, can be used to treat flue gas containing different concentrations of nitric oxide, is beneficial to the prevention and control of air pollution and the efficient production of high-value-added product ammonia, and has good practical application prospects.

[0090] The third aspect of the present invention provides a photocatalyst prepared by the method described in the second aspect.

[0091] The fourth aspect of the present invention provides the use of the above-mentioned photocatalyst in photocatalytic reduction of NO to generate ammonia. The photocatalyst provided by the present invention is used for photocatalytic reduction of NO to generate ammonia, which can improve the photocatalytic activity and ammonia selectivity.

[0092] A fifth aspect of the present invention provides a method for photocatalytic reduction of NO to generate ammonia, the method comprising: contacting a photocatalyst with a NO-containing gas under light irradiation conditions, wherein the photocatalyst is the photocatalyst described in the first aspect or the third aspect above.

[0093] The present invention has a wide range of specific operations and conditions for photocatalytic NO reduction to generate ammonia. Preferably, the photocatalyst is provided in the form of a mixed solution, in which the ratio of photocatalyst to solvent is 4-6 mg: 40-60 mL.

[0094] The present invention has a wide range of solvents to choose from, which may be water and / or an organic solvent (preferably ethylene glycol). Preferably, the volume ratio of water to ethylene glycol in the solvent is 30-55:4-6.

[0095] The method provided by the present invention can treat NO-containing gases of different concentrations. Preferably, the volume concentration of NO in the NO-containing gas is 1-100%, for example, 1%, 10%, 20%, 50%, 70%, 90%, 100%.

[0096] There is no particular limitation on the types of components other than NO in the NO-containing gas, which is subject to the actual gas to be treated.

[0097] Preferably, the conditions of the contact reaction include: performing a photocatalytic reaction for 0.5-2h under 180-320W light conditions.

[0098] The light source includes but is not limited to a 300w Xe full-spectrum irradiation lamp and a cutoff filter.

[0099] According to a preferred embodiment of the present invention, the method for photocatalytic NO reduction to generate ammonia comprises: placing a photocatalyst in a reactor in the form of a mixed liquid, introducing a NO-containing gas for bubbling, removing air and sealing; placing the reactor under a light source for irradiation to react. Preferably, the flow rate of the NO-containing gas is 10-30 sccm, and the bubbling time is 10-50 min.

[0100] The present invention will be described in detail below through examples.

[0101] In the following examples, TEM characterization and EDS characterization were performed on a microscope model JEM 2100 produced by JEOL Corporation of Japan, with an accelerating voltage of 200 kV.

[0102] XRD characterization was performed using a BRUKER brand D8 / Advance X-ray diffractometer (Cu Kα x-ray: λ=0.1545 nm).

[0103] XPS characterization was performed using an ESCALab250XI photoelectron spectrometer from Thermo Fisher Scientific, USA.

[0104] UV / Vis-NIR characterization was performed using a PerkinElmer Lambda 900 spectrometer.

[0105] ESR characterization was performed using a Bruker A300-10 / 12 electron spin resonance spectrometer from Germany.

[0106] Example 1

[0107] This example is used to illustrate the preparation of photocatalyst.

[0108] (a) 400 mg MoO 3 Disperse in 20 mL of water, stir and heat in a water bath at 80 °C for 30 min to obtain MoO 3 Dispersion; To MoO 3 98.06 mg Na was added to the dispersion 2 PdCl 4 and 11.36 mg CuCl 2 ·2H 2 O powder (Na 2 PdCl 4 and CuCl 2 ·2H 2 O molar ratio is 5:1), stirred and then allowed to stand for 1 hour;

[0109] (b) adding 210 mg of polyvinyl pyrrolidone K-30 (PVP), 240 mg of L-ascorbic acid and 600 mg of potassium bromide (KBr) to the solution of step (a), and stirring magnetically for 3 h; then centrifuging ultrapure water to remove PVP, L-ascorbic acid and KBr, and leaving the precursor solution to stand for 2 hours;

[0110] (c) The precursor material obtained in step (b) was washed with ethanol, centrifuged at 10000 r / min, and then placed in a 60°C vacuum oven (vacuum degree of -3000 kPa) for drying for 6 h to obtain Pd 0 CuO / MoO 3 powder;

[0111] (d) Pd obtained in step (c) 0 CuO / MoO 3 The powder was placed in a tube furnace at 320°C and H 2 PdCu / H can be obtained by calcining in atmosphere for 1 h. x MoO 3-y Hybrid photocatalysts.

[0112] TEM results of the photocatalyst are shown in Figure 1 As shown by Figure 1 It can be seen that in H x MoO 3-y PdCu alloy nanoparticles with spherical-like size (~5 nm) and shape were deposited on the nanosheets;

[0113] Figure 2 The PdCu / H prepared in Example 1 x MoO 3-y TEM image of the photocatalyst and the corresponding energy dispersive X-ray spectroscopy (EDS) image; the yellow line in a represents the range of EDS scanning, corresponding to the horizontal axis in b, which represents the type and quantity of elements in the catalyst sample within the scanned range. Figure 2 It can be seen that PdCu / H x MoO 3-y The spatial distribution of Pd and Cu elements in the hybrid is the same. Figure 1 and Figure 2 The formation of PdCu alloy is fully demonstrated.

[0114] Depend on Figure 3 It can be seen that PdCu / H x MoO 3-y The XRD spectrum of the hybrid mainly points to the orthogonal H 0.34 MoO 3 phase (PDF#34-1230), Pd and Cu nanoparticles have no obvious diffraction peaks, indicating that PdCu in H x MoO3-y Highly dispersed.

[0115] Example 2

[0116] According to the method of Example 1, except that in step (a), MoO 3 107 mg Na was added to the dispersion 2 PdCl 4 and 6.2 mg CuCl 2 ·2H 2 O powder (Na 2 PdCl 4 and CuCl 2 ·2H 2 O has a molar ratio of 10:1).

[0117] Example 3

[0118] According to the method of Example 1, except that in step (a), MoO 3 58.9 mg Na was added to the dispersion 2 PdCl 4 and 34.1 mg CuCl 2 ·2H 2 O powder (Na 2 PdCl 4 and CuCl 2 ·2H 2 O has a molar ratio of 1:1).

[0119] Comparative Example 1

[0120] The method of Example 1 is followed, except that in step (a), Na 2 PdCl 4 and CuCl 2 ·2H 2 The molar ratio of Na and O is 1:0, that is, 117.7 mg Na 2 PdCl 4 and 0 mg CuCl 2 ·2H 2 O.

[0121] Comparative Example 2

[0122] The method of Example 1 is followed, except that in step (a), Na 2 PdCl 4 and CuCl 2 ·2H 2 The molar ratio of O is 0:1, that is, 0 mg Na 2 PdCl 4 and 68.2 mg CuCl 2·2H 2 O.

[0123] Comparative Example 3

[0124] The method of Example 1 is followed, except that in step (a), Na 2 PdCl 4 and CuCl 2 ·2H 2 The molar ratio of O is 0:0, that is, 0 mg Na 2 PdCl 4 and 0 mg CuCl 2 ·2H 2 O.

[0125] The X-ray photoelectron spectroscopy (XPS) of the photocatalysts prepared in Examples 1-3 and Comparative Examples 1-3 is shown in FIG. Figure 4 As shown by Figure 4 It can be seen that MoO 3 Only Mo exists in 6+ species, while the photocatalyst prepared in Comparative Example 3 contains both Mo 6+ and Mo 5+ In the photocatalysts prepared in Examples 1-3 and Comparative Examples 1-2, the oxidation states of Mo are Mo 6+ 、Mo 5+ and Mo 4+ Three forms, indicating that H overflow caused the partial reduction of Mo.

[0126] Depend on Figure 5 It can be seen that the photocatalysts prepared in Examples 1-3 and Comparative Examples 1-3 and MoO 3 The O 1sXPS spectra of the samples have three peaks, namely 532.4eV and -OH coordinated with Mo atoms. 2 (O H2O ) group, 531.4eV -OH group coordinated with Mo atom (O -OH ) and 530.85 eV of the lattice O atom coordination group (O latt ). with MoO 3 In comparison, the peak intensity of the -OH component in the photocatalysts prepared in Examples 1-3 and Comparative Examples 1-3 was significantly enhanced, proving the existence of the Mo-OH bond. -OH +O H2O ) / O total The ratios are MoO 3 <Comparative Example 3<Comparative Example 2<Comparative Example 1<Examples 1-3, further indicating that the photocatalysts prepared in Examples 1-3 contain H + The degree of intercalation is high.

[0127] Depend on Figure 6It can be seen that the Pd species in the photocatalysts prepared in Examples 1-3 and Comparative Example 1 are all Pd 0 The Cu 2p XPS spectrum of the photocatalyst prepared in Comparative Example 2 did not show any peaks, indicating that it is difficult for Cu to be loaded on H alone. x MoO 3-y With the addition of Pd, the binding energy is 950.9eV (2p 1 / 2 ) and 931.6eV(2p 3 / 2 ) can be well supported on H in the form of PdCu alloy. x MoO 3-y In addition, the XPS peak of Pd 3d of the photocatalyst prepared in Examples 1-3 is significantly shifted relative to the XPS peak of Pd 3d of the photocatalyst prepared in Comparative Example 1, which indicates that there is a strong charge transfer and electronic interaction between Cu and Pd. Figure 1-Figure 6 It shows that PdCu / H was successfully prepared x MoO 3-y Hybrid photocatalysts.

[0128] Depend on Figure 7 It can be seen that Example 1 has a strong LSPR absorption peak at about 540nm in the visible light range, the LSPR peak intensity and position of Comparative Example 1 are similar to those of Example 1, and the LSPR peaks of Comparative Examples 2 and 3 are significantly red-shifted, which indicates that PdCu alloy and Pd nanoparticles can promote the absorption of MoO in the process of H overflow. 3 The generation of oxygen vacancies in the nanostructured carbon nanotubes induces a stronger plasma absorption peak.

[0129] Depend on Figure 8 It can be seen that at g = 2.003, the order of ESR signal intensity is Example 1 > Comparative Example 1 > Comparative Example 2 > Comparative Example 3, which is consistent with Figure 7 The light absorption properties of the mesocatalysts are in the same order, indicating that there are more unpaired free electrons around oxygen vacancies in Example 1.

[0130] Example 4

[0131] According to the method of Example 1, except that in step (a), MoO 3 107.9 mg Na was added to the dispersion 2 PdCl 4 and 5.7 mg CuCl 2 ·2H 2 O powder (Na 2 PdCl 4 and CuCl 2 ·2H 2 O has a molar ratio of 11:1).

[0132] Example 5

[0133] According to the method of Example 1, except that in step (a), MoO 3 39.2 mg Na was added to the dispersion 2 PdCl 4 and 45.5 mg CuCl 2 ·2H 2 O powder (Na 2 PdCl 4 and CuCl 2 ·2H 2 O has a molar ratio of 0.5:1).

[0134] The compositions and structural parameters of the catalysts prepared in the above examples and comparative examples are listed in Table 1 below.

[0135] Table 1

[0136] Pd, mol% Cu, mol% Pd:Cu molar ratio <![CDATA[(O -OH +O H2O ) / O total ]]> Example 1 9.92 1.98 5:1 0.621 Example 2 11.18 1.12 10:1 0.600 Example 3 5.85 5.85 1:1 0.606 Comparative Example 1 11.6 0 1:0 0.589 Comparative Example 2 0 <0.001 0:1 0.564 Comparative Example 3 0 0 0:0 0.473 Example 4 11.37 1.03 11:1 Example 5 3.87 7.73 0.5:1

[0137] Test Case

[0138] The photocatalytic NO reduction performance of the photocatalysts prepared in the above examples and comparative examples was tested.

[0139] The total volume of the photocatalytic reactor is about 100 mL. 5 mg of sample catalyst powder is dispersed in a mixture of 45 mL of water and 5 mL of ethylene glycol (EG). A 300wXe full-spectrum irradiation lamp with different cutoff filters is used as a light source and placed above the reactor. Before the reaction, different volume concentrations of NO (1%, 5%, 10%, 25%, 50%, 99.9%, and the balance is argon) are used to bubble for 30 minutes at a gas flow rate of 20 sccm. The air is removed and the photoreaction is carried out for 1 hour after sealing. Then, the possible liquid product NH is analyzed by Nessler's reagent spectrophotometer and 1H nuclear magnetic resonance (1H-NMR) method. 3 and NH 2 OH was analyzed and quantified, and possible gas products (N 2 、N 2 O, H 2 The samples were analyzed and quantified by gas chromatography (GC9790Plus, Agilent).

[0140] In order to test the photocatalytic activity of photocatalysts in alkali metal solutions and heavy metal solutions, relevant experiments were designed. The photocatalytic activity test of photocatalysts in alkali metal solutions was as above, except that the above 45 mL of water and 5 mL of ethylene glycol (EG) were replaced by 45 mL of Na2O3 with a concentration of 50 mg / L. 2 SO 4The photocatalytic activity of the photocatalyst in the heavy metal solution was tested as above, except that the above 45 mL of water and 5 mL of ethylene glycol (EG) were replaced by 45 mL of 50 mg / L (CH 3 COO 2 Cd solution and 5 mL of ethylene glycol (EG).

[0141] Fig. 9 The photocatalysts prepared in Examples 1-5 and Comparative Examples 1-3 showed NH 3 and NH 2 The yield of OH, from Fig. 9 It can be seen that by x MoO 3-y Pd nanoparticles and PdCu alloy were deposited on the surface of the substrate to photocatalyze the NO reduction reaction (NORR) of NH 3 The photocatalytic performance of the synthesized NH 3 The yield is significantly higher than that of Comparative Examples 1-3, which indicates that the alloy structure can improve NH 3 Yield.

[0142] Depend on Fig.10 It can be seen that under various monochromatic light irradiations, by calculating the PdCu / H prepared in Example 1 x MoO 3-y The apparent quantum efficiency (AQE) of the hybrids was used to study the light utilization efficiency. Fig.10 The AQE reaches a maximum value of 2.8 at 540 nm, which indicates that PdCu / H x MoO 3-y The improved performance of the hybrids is due to the LSPR effect induced by oxygen vacancies. Fig.11 It can be seen that Example 1 and Comparative Examples 1-3 show similar activities under light of longer wavelengths (λ>420nm, λ>520nm, λ>800nm), which further effectively verifies that the improvement of the catalytic performance of the photocatalyst is mainly due to the LSPR effect.

[0143] Fig.12 The photocatalytic activity of the photocatalyst prepared in Example 1 under different NO concentrations is shown in FIG. Fig.12 It can be seen that as the NO concentration gradually increases from 1% to 99.9%, the PdCu / H prepared in Example 1 x MoO 3-y Hybrid photocatalysts produce NH 3 The amount of NH 2 The production of OH was highly suppressed, highlighting the NH 3 High selectivity.

[0144] Fig.13 The photocatalyst prepared in Example 1 produces NH 3 The cycle test is carried out by Fig.13 It can be seen that in the 10 cycle tests, NH 3 Although the yield showed a slight downward trend, it still remained at a very high level, indicating that the prepared photocatalyst had excellent stability.

[0145] Fig.14 The photocatalytic activity of the photocatalysts prepared in Example 1 and Comparative Examples 1-3 in alkali metal solutions is: Fig.15 The photocatalytic activity of the photocatalysts prepared in Example 1 and Comparative Examples 1-3 in heavy metal solutions. Fig.14 and Fig.15 It can be seen that the photocatalyst prepared in Example 1 has good alkali resistance and heavy metal resistance.

[0146] The preferred embodiments of the present invention are described in detail above, but the present invention is not limited thereto. Within the technical concept of the present invention, the technical solution of the present invention can be subjected to a variety of simple modifications, including the combination of various technical features in any other suitable manner, and these simple modifications and combinations should also be regarded as the contents disclosed by the present invention and belong to the protection scope of the present invention.

Claims

1. A photocatalyst, characterized in that: The photocatalyst includes H x MoO 3-y , Pd element and Cu element, 0<x≤1, 0≤y<3, wherein, based on the total amount of the photocatalyst, the content of the Pd element is 5-12 mol %, and the content of the Cu element is 0.9-9 mol %.

2. The catalyst according to claim 1, wherein Based on the total amount of the photocatalyst, the content of the Pd element is 5.5-12 mol %, and the content of the Cu element is 1-6 mol %; Preferably, the molar ratio of Pd element to Cu element is 0.5-12:1, preferably 1-10:1; Preferably, based on the total amount of the photocatalyst, the total molar content of the Pd element and the Cu element is 10-13%, preferably 11-12%.

3. The catalyst according to claim 1, wherein The Pd element and the Cu element are at least partially present in the form of a PdCu alloy, preferably dispersed in H x MoO 3-y On nanosheets; Preferably, dispersed in H x MoO 3-y The size of PdCu particles on the nanosheets is 2-10 nm; Preferably, there are no diffraction peaks of Pd and Cu in the XRD spectrum of the photocatalyst.

4. The catalyst according to any one of claims 1 to 3, wherein XPS characterization shows that in the photocatalyst, (O -OH +O H2O ) / O total The molar ratio is 0.6-0.65, preferably 0.6-0.63; Among them, O -OH is the -OH group coordinated with the Mo atom, O H2O is the -OH2 group coordinated with the Mo atom, O total is the total oxygen-containing groups in the sample catalyst.

5. A method for preparing a photocatalyst, the method comprising the following steps: (1) providing a mixed solution containing a molybdenum precursor, a Pd precursor, a Cu precursor, a structure directing agent, a reducing agent, and an ion exchanger; (2) The precursor material obtained from the mixed solution in step (1) is washed and then calcined in a hydrogen atmosphere.

6. The method according to claim 5, wherein: The structure directing agent is an alloy structure directing agent, preferably polyvinyl pyrrolidone; and / or, the reducing agent is L-ascorbic acid; And / or, the ion exchanger is potassium bromide; And / or, the molybdenum precursor is selected from at least one of molybdenum trioxide, ammonium molybdate and sodium molybdate; And / or, the Pd precursor is selected from at least one of sodium chloropalladate, palladium chloride and palladium nitrate; And / or, the Cu precursor is selected from at least one of copper chloride, copper nitrate, copper acetate and copper sulfate.

7. The method according to claim 5 or 6, wherein: The preparation of the mixed solution in step (1) comprises: (1-1) mixing a molybdenum precursor dispersion with a Pd precursor and a Cu precursor; (1-2) mixing the mixed solution obtained in step (1-1) with a structure directing agent, a reducing agent and an ion exchanger; Preferably, the molybdenum precursor and water are mixed and then heated in a water bath under stirring conditions to obtain the molybdenum precursor dispersion.

8. The method according to claim 7, wherein: The concentration of the molybdenum precursor in its aqueous solution is 10-30 g / L; And / or, the conditions for water bath heating include: water bath temperature of 70-90° C., heating time of 20-40 min.

9. The method according to any one of claims 5 to 8, wherein: Calculated on the basis of metal elements, the molar ratio of the Pd precursor to the Cu precursor is 0.5-12:1, preferably 1-10:1; Preferably, the amount of the Pd precursor, the Cu precursor and the molybdenum precursor is such that the total molar content of the Pd element and the Cu element in the prepared photocatalyst is 10-13%, preferably 11-12%, based on the total amount of the photocatalyst; Preferably, relative to the total amount of 0.4 mmol of the Pd precursor and the Cu precursor added, the amount of the structure directing agent is 100-300 mg, the amount of the reducing agent is 100-300 mg, and the amount of the ion exchanger is 500-700 mg.

10. The method according to any one of claims 5 to 9, wherein: The method further comprises, before step (2), removing the structure directing agent, the reducing agent and the ion exchanger in the mixed solution of step (1), and then allowing the mixed solution to stand to obtain the precursor material; Preferably, the washing agent used in the washing is an organic solvent, preferably ethanol; Preferably, the method further comprises drying after the washing, and then performing the calcination, wherein the drying conditions include: a drying temperature of 50-80° C., a vacuum degree of -3000 to -1000 kPa, and a drying time of 4-10 h; Preferably, the calcination conditions in step (2) include: a temperature of 200-400° C. and a calcination time of 0.5-2 h; Preferably, the hydrogen-containing atmosphere is provided by hydrogen and optionally an inert gas.

11. A photocatalyst prepared according to the method according to any one of claims 5 to 10.

12. Use of the photocatalyst according to any one of claims 1 to 4 and 11 in photocatalytic reduction of NO to generate ammonia.

13. A method for photocatalytic reduction of NO to generate ammonia, the method comprising: Under light irradiation conditions, a photocatalyst is contacted with a gas containing NO to react, wherein the photocatalyst is the photocatalyst according to any one of claims 1 to 4 and 11; Preferably, the photocatalyst is provided in the form of a mixed solution, in which the ratio of photocatalyst to solvent is 4-6 mg: 40-60 mL; Preferably, the volume concentration of NO in the NO-containing gas is 1-100%; Preferably, the conditions of the contact reaction include: performing a photocatalytic reaction for 0.5-2h under 180-320W light conditions.

Citation Information

Patent Citations

  • Pt-Ag / WO3 plasma photocatalyst as well as preparation method thereof and application

    CN107790127A

  • HxMoO3-y nanomaterial, HxMoO3-y electrode, solar cell comprising the electrode, and preparation method

    CN108899422A

  • Reduced MoO3-x photocatalyst and production method and application thereof

    CN110013844A

  • Preparation and application of low-palladium metal anchored bismuth molybdate photocatalyst rich in surface oxygen defects

    CN111495362A

  • Oxygen vacancy modified MoO3-x / Fe-W18O49 photocatalyst as well as preparation and application thereof in nitrogen fixation

    CN115069262A